Peformance of Broiler Chickens Fed Differntly Processed Red Kidney Beans Seed Meal (Phaseoulus Vulgaris) as Poultry Feed Resource (British Journal of Multidisciplinary and Advanced Studies, 2023)
An 8 weeks feeding trial was conducted to evaluate the nutritive contribution of red kidney bean (phaseoulus vulgaris) seed meal on growth performance, carcass and internal organ characteristics and economics of production of broiler chickens. Two hundred (Anak-2000) white strain day old broiler chicks were weight and assigned to five groups of forty chicks each. Each group was further divided into four groups of ten birds per replicate in completely randomized design. Five diets were formulated using differently processed Red kidney bean seed meal (Phaseoulus vulgaris) at 0% in the control (T1) and 25% levels of inclusion for Raw (RRKBSM), Toasted (TRKBSM), boiled (BRKBSM) and Dehaulled (DRKBSM) respectively. Feed and water were given ad-libtum daily throughout the feeding trial. The growth performance showed significant (P